Case Report: Wide spectrum of SALL1 variants—a rare cause of pediatric chronic kidney disease - Filipič, Martina; Stangler Herodež, Špela; Močnik, Mirjam; Golob Jančič, Sonja; Marčun Varda, Nataša; Krgović, Danijela (Frontiers in Pediatrics, 2025)
IntroductionGenetic causes of chronic kidney disease present a diverse group. Some of them are associated with extrarenal malformations, especially ear anomalies. Genetic diagnosis is essential to confirm the diagnosis, search for additional potential manifestations, and predict the prognosis.Case presentationWe report a case of a 10-year-old girl with elevated creatinine in whom the presence of auricular appendices led to clinical suspicion of a genetic cause of chronic kidney disease. After investigation, Townes-Brocks syndrome was confirmed with the absence of anorectal and limb abnormalities. Therefore, it can be less apparent and needs to be suspected of.ConclusionRare causes of renal diseases can be suspected already after examination. Malformations of the ears are particularly associated with chronic kidney disease, which should be screened for in such cases. Genetic confirmation allows for the establishment of diagnosis and comprehensive management.SummaryTownes-Brocks syndrome highlights the importance of chronic kidney disease suspicion in a child when malformations of the ears are present in a child.